The Brewer of Preston by Andrea Camilleri - Bianca Maria Balestra (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In contemporary Italian literature Andrea Camilleri’s career as a writer represents a successful story: in a couple of decades he has sold hundreds of thousands copies, has been translated into many languages, has won several awards, his books have been object of workshops. One of his best known works is Il birraio di Preston, a historical novel. At first Camilleri has won public success as the author of detective stories, with the police commissioner Montalbano as the main hero. At a later stage readers have started to appreciate his historical novels too, though they chronologically precede the Montalbano series. However, his historical novels are not less engaging than his detective stories. Camilleri, indeed, knows how to keep the reader's attention alive to the very last page, regardless of genres. This is partly due to the know-how gained during his longtime work for the theatre, the radio and the television, where he has acquired a remarkable experience in dealing with different texts and narrative strategies. Il birraio di Preston finds itself at a turning point in the writer’s career as regards his linguistic and narrative experimentalism, as well as the reader's attention